THE RELATIONSHIP BETWEEN WORKLOAD WITH WORK STRESS ON NURSES IN INTENSIVE INSTALLATION OF BANGIL GENERAL HOSPITAL PASURUAN DISTRICT - Nanang - Fachruddin; WINDU SANTOSO; ANA ZAKIYAH (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Work stress due to excessive demands on the workplace is a problem of human resource management in the hospital. The high workload is one of the factors that cause work stress for nurses. The purpose of this study was to determine the relationship between workload and work stress on nurses in the Intensive Care Unit at Bangil Hospital. The design of this study was an analytic survey using cross-sectional study. The population of all nurses working in the Intensive Care Installation with a sample of 40 respondents and using purposive sampling technique. Workload instruments use work sampling observation sheets, while work stress instruments use questionnaires based on Sulsky and Smith's theory of Jusnimar, (2012) modified. The results of the study using Spearman rho showed a relationship between workload and work stress on nurses with p-value = 0.000 (<0.05) and an r-value of 0.551. The level of dependency of the client and the amount of labor that is not appropriate is a factor of high workload so that nurses experience work stress. There needs to be an evaluation of the number of nurse needs or the provision of rewards and stress management training for nurses to adapt and control work stress.